Microstructural evolution and mechanical property enhancement of red mud incorporated high strength concrete - Chava Venkatesh; Chereddy Sonali Sri Durga; Takkellapati Sujatha; Ramamohana Reddy Bellum; Bypaneni Krishna Chaitanya; Meseret Getnet Meharie (Scientific Reports)
Abstract This study investigates the effects of red mud (RM) incorporation on high-strength concrete through comprehensive assessment of mechanical properties, microstructural characteristics, and phase evolution over 180 days. Five concrete mixtures with RM replacement levels ranging from 0 to 20% were analyzed. Results demonstrate that 10% RM replacement achieves superior performance with 28.96%, 13.66%, and 15.45% improvements in compressive, split tensile, and flexural strengths respectively at 180 days. X-ray diffraction analysis reveals significant mineralogical transformation in this mixture, with progressive reduction in portlandite content and increased formation of strength-contributing phases. Scanning electron microscopy confirms enhanced matrix densification and improved interfacial transition zone characteristics, while Energy Dispersive X-ray analysis shows a favorable Ca/Si ratio of 0.9475 at 180 days, indicating formation of stable C-S-H gel structures. Novel prediction models for mechanical properties demonstrate greater accuracy compared to established code equations. This research establishes 10% as the most effective RM replacement threshold, balancing enhanced mechanical performance with sustainability benefits, thereby providing a robust framework for industrial-scale implementation of RM in high-strength concrete applications.